NETS1HD: Study protocol for development of a core outcome set for use in determining the overall success of Hirschsprung's disease treatment - Allin, B; Bradnock, T; Kenny, S; Walker, G; Knight, M (BioMed Central, 2016)
Background: Use of core outcome sets in research has been proposed as a method for countering the problems caused by heterogeneity of outcome measure reporting. Heterogeneity of outcome measure reporting occurs in Hirschsprung’s disease (HD) research and is limiting the development of a robust evidence base to support clinical practice. Methods: Candidate outcome measures have been identified through a systematic review. These outcome measures will form the starting point for a three-phase online Delphi process to be carried out in parallel by three panels of experts. Panel 1 is a neonatal panel; panel 2 is a non-neonatal panel; and panel 3 is a lay panel. In round 1, experts will be asked to score the previously identified outcome measures from 1 to 9 based on how important they think the measures are in determining the overall success of their/their child’s/their patient’s HD. In round 2, experts will be presented with the same list of outcome measures and graphical representations of how their panel scored that outcome in round 1. They will be asked to re-score the outcome measure, taking into account how important other members of their panel felt it to be. In round 3, experts will again be asked to re-score each outcome measure, but this time they will receive a graphical representation of the distribution of scores from all three panels, which they should take into account when re-scoring. Following round 3 of the Delphi process, 40 experts will be invited to attend a face-to-face consensus meeting. Participants will be invited in a purposive manner to obtain balance between the different panels. Results of the Delphi process will be discussed, and outcomes will be re-scored. Outcome measures where >70% of participants at the meeting scored it 7–9 and <15% scored it 1–3 will form the core outcome set. Discussion: Development of a core outcome set will help to reduce heterogeneity of outcome measure reporting in HD. This will increase the quality of research taking place and ultimately improve care provided to infants with HD.